Lemon Sign: The Diagnostic Indicator for Spina Bifida - Regina P.F. (International Journal of Midwifery Nursing And Practices, 2026)
The “lemon sign” is a distinctive ultrasonographic finding that serves as a diagnostic indicator for spina bifida, a congenital neural tube defect characterized by incomplete closure of the spinal cord. This sign is observed in fetal imaging and is considered an early and reliable marker for detecting spina bifida, particularly when combined with other prenatal diagnostic tools such as the “banana sign.” The lemon sign is characterized by a flattened, concave appearance of the fetal skull, which occurs due to the herniation of the cerebellum and the posterior displacement of the brain. This deformation is a result of the loss of normal intracranial pressure, commonly associated with spina bifida. The identification of the lemon sign during routine fetal ultrasound can significantly aid in early diagnosis, allowing for timely intervention and management decisions. Prenatal diagnosis using ultrasound plays a crucial role in the management of spina bifida, as it enables healthcare providers to offer appropriate counselling, surgical intervention options, and postnatal care planning. This article explores the pathophysiology, clinical significance, and diagnostic accuracy of the lemon sign in detecting spina bifida, providing an overview of how this marker contributes to the diagnosis and subsequent treatment strategies.
Keywords: Lemon sign; fetal ultrasound; neural tube defect; prenatal diagnosis; spina bifida